Sorvegliare gli adulti punendo i bambini (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article addresses the issue of the admissibility of birth certificates of children born abroad through surrogacy, starting from the recent Constitutional Court decision no. 33 of 2021. The instrument of analogia and the representation of public international order as a set of principles and rules structurally organized constitute the “point of view” from which the Constitutional Court’s conclusions are subjected to critical examination.
Keywords: Surrogacy; best interests of the child; woman’s dignity; international public order; analogy